How the market is changing China's news the case of Xinhua News Agency - Xin, Xin 1972- (Lexington Books, 2012)
This book provides a micro-analysis of the impact of marketisation and globalization on China's media system over the last three decades with a focus on Xinhua News Agency - one of the most influential propaganda apparatuses of the Chinese Communist Party. It investigates not only Xinhua itself, but also its evolving relations with news sources, media clients and other social institutions